A Model for Promoting Poultry Industry Development in Togo: Part 1. Management Practices and Incubation Conditions - Tona , K.; Agbonon, A.; Eklu-Gadegbeku, K.; Teteh, A.; Simons, P.; Buyse, J.; Everaert, N.; Kemp, B.; Decuypere, E.; Gbeassor, M. (International Journal of Poultry Science, 2014)
In commercial poultry husbandry practice, the hatchery takes over the incubation of bird eggs in order to provide as many day-old chicks as needed at any time to farmers. The main bottleneck for poultry industry development in Togo is the lack of day-old chick supply. Indeed, there is no proficient hatchery which can cover the needs of the farmers because of lack of information about hatchery management or people trained as hatchery managers. Also, there is lack of information about management practice aspects, etc. With the aim to promote poultry industry in Togo, an interuniversity project [Catholic University of Leuven (KUL) and University of Lome (UL)] as a model of poultry industry development was implemented. Specific objectives of the current project are to implement research and development activities on better conditions of incubation and adapted management practices focusing mainly on (1) Effect of early transferring of layer breeders hatching eggs on embryo parameters and hatchability, (2) Comparison of different chicken genotypes in Embryo Physiology, (3) Effects of heat conditioning at d 16 to 18 of incubation or during early broiler rearing on embryo physiology, post-hatch growth performance and heat tolerance, (4) Effect of low albumen quantity on chick embryo and post-hatch parameters, (5) Effects of In ovo-administration of L-carnitine on hatching events and juvenile performance of layer-type chick, (6) Interaction effects of mixing hatching eggs of differential embryo growth trajectory and incubator CO2concentration on embryo physiological parameters, (7) Effect of delayed feed access on production and blood parameters of layer-type chicks and (8) Induced moulting of layer chickens.